Work Discipline as the Strongest Determinant of Employee Performance: Evidence from Local Government in a Developing Region of Indonesia - Heluka, Isak; Rante, Yohanis; Ratang, Westim (Magister Manajemen Universitas Cenderawasih, 2025)
Human resources are a critical determinant of organizational success, particularly in the public sector. Employee performance is influenced by several factors, including leadership, work motivation, and work discipline, which remain challenges in regional government institutions such as the Department of Industry, Trade, Cooperatives, and SMEs in Yahukimo Regency, Indonesia. This study aims to examine the influence of leadership, work motivation, and work discipline on employee performance, both partially and simultaneously. A causal-comparative research design with a quantitative approach was employed. The population consisted of all 37 employees of the department, who were included as a saturated sample. Data were collected through questionnaires, interviews, observations, and documentation, and analyzed using multiple linear regression with classical assumption tests, t-tests, and F-tests. The findings reveal that leadership, work motivation, and work discipline each have a significant positive effect on employee performance. Simultaneously, the three variables explain 51.1% of the variance in performance, with work discipline contributing the strongest effect, followed by motivation and leadership. The results highlight the importance of strengthening leadership practices, implementing effective motivational strategies, and enforcing consistent work discipline to improve organizational performance in the public sector. This study contributes empirical evidence to the human resource management literature in developing regions and provides practical recommendations for local governments to enhance civil servant performance.